Factors that Influence of Behavior to Contribution in Islamic Peer-to-Peer Lending with PLS-SEM Approach: Empirical Studies in Indonesia - Azidni Rofiqo; Ahmad Suminto; Daud Sukoco; M. Ali Ramadhan; Diyan Novita Sari (Journal of Islamic Economics Lariba, 2022)
This study aims to develop a Theory of Planned Behavior by analyzing the factors that influence customers to contribute to Islamic P2P lending customers. This study uses a partial least squares structural equation model (PLS-SEM) analysis with 120 respondents. The number of respondents is determined by the five rules of thumb approach, while data collection is done by purposive sampling. This research was conducted for one year, namely in 2021-2022 with the provision that the sample was customers of Islamic P2P lending in Indonesia. The results of the study revealed that attitude, subjective norm and perceived behavior control had a significant positive effect on the intention to contribute to Islamic P2P lending. While piety and intention have a significant positive effect on behavior to contribute to Islamic P2P lending in Indonesia. The results of this study contribute to the development of the theory of planned behavior (TPB), more extensive research is needed such as research in countries that are members of the OIC to validate these results. Keywords: Muslim Behavior, Islamic Peer-to-Peer Landing, Financial Technology